2009
DOI: 10.1177/0969733009106647
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients’ Perceptions of the Good Nurse: a Literature Review

Abstract: This article discusses findings from a mixed method literature review that investigated cancer patients' perceptions of what constitutes a good nurse. To find pertinent articles, we conducted a systematic key word search of five journal databases (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). The appli cation of carefully constructed inclusion criteria and critical appraisal identified 12 relevant articles. According to the patients, good nurses were shown to be characterized by specific, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 38 publications
4
80
0
10
Order By: Relevance
“…In particular, research conducted with people from Europe, the Middle East, Africa, and the USA has all found that patients describe good patient-nurse relationships as encompassing trust, emotional support and being treated as an individual and as allowing them to feel secure enough to depend on and share their fears with the nurse (Ramos 1992, P alsson & Norberg 1995, Deeny & McGuigan 1999, Coffey 2006, Dowling 2008, Rchaidia et al 2009, Beaver et al 2010, Kristiansen et al 2010, Remmers et al 2010. If the nursepatient relationship has characteristics of an attachment relationship, we should expect that patients' attachment models would influence their experience of the relationship.…”
Section: Nurses As Attachment Figures?mentioning
confidence: 99%
“…In particular, research conducted with people from Europe, the Middle East, Africa, and the USA has all found that patients describe good patient-nurse relationships as encompassing trust, emotional support and being treated as an individual and as allowing them to feel secure enough to depend on and share their fears with the nurse (Ramos 1992, P alsson & Norberg 1995, Deeny & McGuigan 1999, Coffey 2006, Dowling 2008, Rchaidia et al 2009, Beaver et al 2010, Kristiansen et al 2010, Remmers et al 2010. If the nursepatient relationship has characteristics of an attachment relationship, we should expect that patients' attachment models would influence their experience of the relationship.…”
Section: Nurses As Attachment Figures?mentioning
confidence: 99%
“…Cancer patients have consider good communication based on trust and being seen as important aspects of highquality nursing. 23,24,26 These care characteristics promote their dignity. 26,27 Trust, which usually entails a transition of power to a person (eg, a nurse) or a system (eg, a hospital) to act on one's behalf, must be shared to be maintained.…”
Section: Findings Compared With a Strength Perspective In Cancer Resementioning
confidence: 99%
“…For example, Rchaidia et al (2008) in a Belgium study found that cancer patients' perceptions of good nurses were very much focused into how caring nurses are and the importance of person-to-person relationships and compassionate care that nurtures patients' well-being. In a Polish study Marcinowicz et al (2009) examines the attributes that medical students consider important for nurses.…”
Section: Discussionmentioning
confidence: 99%